PELATIHAN SENAM WAJAH UNTUK MENCEGAH GANGGUAN BICARA PADA LANSIA - Hanif Afida; Jenni Marsella Br Barrus; Muhammad Dicky Maulana; Shiane Hanako Sheba (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2025)
Speech disorders such as dysarthria in the elderly can reduce communication skills and independence if preventive measures are not taken early on. This community service activity aims to increase the knowledge and independence of the elderly in preventing speech disorders such as dysarthria through education and facial exercise training. The activity was held on January 7, 2026, at the Al Islam Polytechnic in Bandung, involving 29 elderly participants. The methods used included interactive lectures, demonstrations and reenactments of facial exercises, as well as evaluations through pre-tests, post-tests, and observations of practical skills. The results of the activity showed an increase in the elderly's knowledge regarding the definition of dysarthria, risk factors, prevention and treatment, as well as an increase in the elderly's ability to perform facial exercises independently. This activity was concluded to be effective in increasing the knowledge and independence of the elderly, and it is recommended to be carried out continuously and expanded to other elderly communities to support promotional and preventive efforts in the field of speech therapy. Keywords: elderly; dysarthria; facial exercises; speech therapy; community service